2022
DOI: 10.3389/fpubh.2021.815631
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Prediction Model for Cancer-Specific Survival of Elderly Patients With Hypopharyngeal Squamous Cell Carcinomas: A Population-Based Study

Abstract: Background: Hypopharyngeal squamous cell carcinomas (HPSCC) is one of the causes of death in elderly patients, an accurate prediction of survival can effectively improve the prognosis of patients. However, there is no accurate assessment of the survival prognosis of elderly patients with HPSCC. The purpose of this study is to establish a nomogram to predict the cancer-specific survival (CSS) of elderly patients with HPSCC.Methods: The clinicopathological data of all patients from 2004 to 2018 were downloaded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, only the size of the tumor, the presence of lymph node metastasis, and distant metastasis were used as criteria. Age, marital status, surgical method, chemotherapy and radiotherapy, and other important factors that have been proven to affect cancer patients' overall survival rate (OS) were ignored ( 31 ). Our study found that in elderly patients undergoing pRCC surgery, partial nephrectomy (PN) had the best prognosis, radical nephrectomy (RN) was intermediate, and local tumor resection had the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the size of the tumor, the presence of lymph node metastasis, and distant metastasis were used as criteria. Age, marital status, surgical method, chemotherapy and radiotherapy, and other important factors that have been proven to affect cancer patients' overall survival rate (OS) were ignored ( 31 ). Our study found that in elderly patients undergoing pRCC surgery, partial nephrectomy (PN) had the best prognosis, radical nephrectomy (RN) was intermediate, and local tumor resection had the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Using the SEER database, another study recruited 3,172 HPSCC patients aged 60 and above years old diagnosed from 2004 to 2018. Multivariate survival analysis indicated that there was no significant difference in cancer specific survival between white and black patients [16]. Kuo et al identified a total of 3,357 adult patients with primary HPSCC without distant metastases from the NCDB between 1998 and 2011.…”
Section: Plos Onementioning
confidence: 99%
“…Several recent studies have built statistical models to predict the prognosis of HPSCC [10][11][12][13][14][15][16]. Race is found to be one of the independent factors correlated with survival in patients with HPSCC in some studies [10][11][12][13], in which black patients were shown to have worse survival compared to whites or other races [10][11][12][13]17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation